2020
DOI: 10.3390/nu12030736
|View full text |Cite
|
Sign up to set email alerts
|

Glycolate is a Novel Marker of Vitamin B2 Deficiency Involved in Gut Microbe Metabolism in Mice

Abstract: Microbes in the human gut play a role in the production of bioactive compounds, including some vitamins. Although several studies attempted to identify definitive markers for certain vitamin deficiencies, the role of gut microbiota in these deficiencies is unclear. To investigate the role of gut microbiota in deficiencies of four vitamins, B2, B6, folate, and B12, we conducted a comprehensive analysis of metabolites in mice treated and untreated with antibiotics. We identified glycolate (GA) as a novel marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The gut microbiota was able to provide compensatory riboflavin in the short-term when a dietary riboflavin deficiency was induced in mice ( Figure 2, Table 1). [43] The survival of axenic-but not conventional-Drosophila was significantly depressed when their diet lacked riboflavin. [44] Qi B et al showed the importance of live bacteria being able to provide micronutrients in the gut, such as riboflavin, to C. elegans (Table 1).…”
Section: Vitamin B2 (Riboflavin)mentioning
confidence: 99%
“…The gut microbiota was able to provide compensatory riboflavin in the short-term when a dietary riboflavin deficiency was induced in mice ( Figure 2, Table 1). [43] The survival of axenic-but not conventional-Drosophila was significantly depressed when their diet lacked riboflavin. [44] Qi B et al showed the importance of live bacteria being able to provide micronutrients in the gut, such as riboflavin, to C. elegans (Table 1).…”
Section: Vitamin B2 (Riboflavin)mentioning
confidence: 99%
“…[ 33–35 ] We previously showed that administration of a vitamin B2 (VB2)‐deficient diet could decrease GO activity in the liver and lessen increases in plasma glycolate concentrations. [ 36 ] We also observed a negative correlation between GO activity in the liver and plasma glycolate concentrations, suggesting that VB2 deficiency in the liver inhibits metabolism of glycolate to glyoxylate due to reduced GO activity. [ 36 ] To explore this possibility, in the present study we investigated whether hyperoxaluria could be suppressed by feeding a VB2‐deficient diet to mice with hydroxyproline‐ or obesity‐induced hyperoxaluria.…”
Section: Introductionmentioning
confidence: 75%
“…[ 36 ] We also observed a negative correlation between GO activity in the liver and plasma glycolate concentrations, suggesting that VB2 deficiency in the liver inhibits metabolism of glycolate to glyoxylate due to reduced GO activity. [ 36 ] To explore this possibility, in the present study we investigated whether hyperoxaluria could be suppressed by feeding a VB2‐deficient diet to mice with hydroxyproline‐ or obesity‐induced hyperoxaluria. A better understanding of how a VB2‐deficient diet can affect hyperoxaluria will facilitate development of more effective therapies.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations